The revenue and double dividend potential of taxes on international private capital flows and securities transactions - Ilene Grabel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper explores two proposals to tax financial flows in developing economies—the package of policies implemented to various degrees by Chile and Colombia during the 1990s, widely referred to today as the Chilean model—and securities transactions taxes (STTs). I find that each provides a viable mechanism to raise revenue in some developing countries. Both can be introduced unilaterally (with the prospect of multilateral coordination in the future); both are progressive in their incidence, and in the case of the STT, represents an administratively manageable form of revenue collection. I also find that each entails double dividends that manifest in greater domestic and international macroeconomic stability.
Keywords: H2; H5; O23; E62; 330; securities transaction taxes; international private capital flows; financing for development; double dividends; taxation; financial flows; Kapitalmobilität; Börsenumsatzsteuer; Entwicklungsfinanzierung